Effect of different adhesive systems and silane application on shear bond strength of resin cement to indirect restorations - Makbule Heval Şahan; Cem Peşkersoy; Övül Kümbüloğlu; Murat Türkün (Mashhad University of Medical Sciences, 2023)
Objective: This study compared the influence of various adhesive systems and silane application on the adhesion of resin-based luting cement to lithium disilicate, indirect composite resin, and zirconia restorations.Methods: Lithium disilicate (n=50), indirect composite resin (n=50), and zirconia (n=50) blocks were divided into five groups (n=10), according to the adhesive protocol applied as follows: 1. Optibond XTR, 2. silane + Optibond All in One, 3. One Coat 7 Universal, 4) Adper Scotchbond Multi-Purpose, and 5) Silane + Single Bond Universal. The blocks were bonded to a resin-based luting cement after surface treatments (silica coating and acid application). The bonded specimens were incubated in 37° C water for 24 hours and thermocycled for 5,000 cycles. The shear bond strength (SBS) was evaluated by a universal testing machine. The adhesion protocols for each type of restoration were compared by one-way ANOVA and Dunnett T3 test.Results: There were significant differences in the bond strength of cement to indirect restorations between various adhesive protocols (P<0.05). In all types of restorations, the highest SBS was observed in group 5, which was silanized and bonded with Single Bond Universal. The bond strength of group 5 in lithium disilicate, indirect composite resin, and zirconia groups were 26.1 ± 4.9 MPa, 20.5 ± 5.7 MPa, and 15.4 ± 4.7 MPa, respectively.Conclusions: It appears that the best adhesive protocol for bonding cement to lithium disilicate, indirect composite resin, and zirconia restorations is the use of silane and a universal adhesive containing silane (Single Bond Universal). (J Dent Mater Tech 2023;12(2): 104-110)